STUDI KASUS : ASUHAN KEBIDANAN PADA Ny.E MASA KEHAMILAN TRIMESTER III, PERSALINAN, NIFAS, NEONATUS DAN KELUARGA BERENCANA - Risa Intan Fitriyani; Ellyzabeth Sukmawati; Dahlia Arief Rantauni (Lembaga Pengembangan Kinerja Dosen, 2022)
This report is a comprehensive midwifery care carried out at the Maos Health Center in 2022 for Mrs. “E” G2P1A0 35 weeks 5 days of pregnancy which was carried out from January to March from the third trimester of pregnancy, maternity, postpartum, newborn and family planning services. The documented Maternal Mortality Rate (MMR) and Infant Mortality Rate (IMR) are indicators to see the welfare of a nation in determining optimal health status (Prawiroharjo, 2016). The number of maternal deaths in Indonesia in 2020 increased by 8.92% from the previous year, which was 4,221 to 4,627 people. One of the efforts made in reducing maternal and infant mortality is increasing quality antenatal care, with the aim of alleviating these morbidity and mortality rates. This report is a comprehensive midwifery care carried out at the Maos Health Center on Ny. “E” G2P1A0 The gestational age of 35 weeks 5 days was carried out from January to March from the third trimester of pregnancy, postpartum, postpartum, neonate and family planning services that were documented with the application of varney management and SOAP documentation. Based on the observations of this Final Project, no gaps were found between theory and practice during the implementation of comprehensive midwifery care provided from the initial visit to the last visit.